COVID-19 language: an analysis of the (new) lexicon used in the pandemic in Peruvian Spanish - Osorio Anchiraico, Trixia (2020)
This article analyzes some of the most used words in the Peruvian press media, virtually documented, related to the pandemic. Based on the selected sample, the aim is to reveal which is the process of word formation most used in the Peruvian language. On the other hand, it is sought to identify if there are some new terms (neologism), and to describe the meaning in the context used.